Effect of nitrogen, phosphate and potassium fertilization on dystrophic soil on the content of secondary metabolites in Hydrocotyle umbellata L. var. bonariensis (Lam.) Spreng (Research, Society and Development, 2021)
The knowledge of medicinal plants is of great importance for popular health. On the other hand, the levels of secondary metabolites in medicinal plants is an important parameter to be evaluated. The study of the nutrition of plants and the production of metabolites can provide the identification of beneficial factors and also find out if there are harmful effects of this fertilization/nutrition. In this study, three experiments were carried out (nitrogen, phosphate and potassium fertilization) in the culture of Hydrocotyle umbellata L. var. bonariensis (Lam.) Spreng on dystrophic Red Latosol on metabolite production (total phenols, total flavonoids and hibalactone content). It was used the soil of a rural property in the municipality of Anápolis – Goiás (Brazil). The experimental design was completely randomized, in a controlled environment. The experiment involved the following dosages of fertilization: nitrogen (0; 30; 45; 60 e 75 kg of N.ha-1); phosphate (0; 120; 150; 180 e 210 kg of P2O5.ha-1) and potassium (0; 25; 50; 75 e 100 kg of K2O.ha-1). The maximum contents of total phenols were with the medium level of nitrogen, zero level of phosphorous and highest level of potassium. For the total flavonoid, the maximum contents were obtained with the medium levels of nitrogen and potassium and zero level of phosphorus. Finally, the hibalactone content was favored by highest level of nitrogen and zero levels of phosphorus and potassium.